(3efGRd GdMQhas - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s ((3eQh GdTGgLGf s)
(3ChdgG (B:s
(3bGd cJGH efGRd GdMQha(B: (3GddGeGJ GKfJG YTQ dGe GHJOGA fMh bhdc(B: (3dRjlO NjQ efc s
(3BNQgG (B:s
(3hEeG Ef bGd(B: (3CfJ WGdb Ef cdepJ RjOkG, aYdi GdJQbH ceG qHjfG, Ke s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3cJHJ GdfSNI Yf fSNI HNW YeQ Hf CHj YeQ GdSLSJGfj GdSLRj ebQDI Ydi GdeUfa SfI (B381 (3aj OGQg HeOjfI GdSdGe hYdjg ELGRJg s
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B175 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B315 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs